The effectiveness of online learning in the mathematics and sciences department: in learning biology - Yenny Anwar; Kodri Madang; Ketang Wiyono; Effendi Nawawi; Hapizah Hapizah; Indah Intan Sari (Sriwijaya University Learning and Education International Journal, 2025)
Since the COVID-19 pandemic, online learning has become commonplace, but the effectiveness of online learning has never been evaluated; therefore, it is necessary to evaluate the effectiveness of online learning. This descriptive study aims to describe the effectiveness of online learning for lecturers and students of the Biology Education Study Program, FKIP Unsri, with a sample of 140 students and 16 lecturers in the odd semester. The study results show that online learning from the aspects of support, facilities and infrastructure, stakeholders, learning processes and student achievement indexes is included in the effective category. The platforms that are often used by students and lecturers besides Unsri e-learning are Google Classroom and several supporting platforms such as Zoom Cloud Meeting and WhatsApp. Applications and platforms, and online-based learning can still be used even though the pandemic has ended, because the online-based learning process is still better when combined with offline learning, which can facilitate direct interaction between students and teachers.